ANALISIS BUKU DIGITAL INTERAKTIF SEBAGAI MEDIA KOMUNIKASI MUSEUM KEPRESIDENAN RI BALAI KIRTI - Tabita, Dinda Hersya; Leonard Dharmawan (NALAR: Jurnal Pendidikan dan Kebudayaan, 2025)
This study aims to identify the factors that influence the implementation of interactive digital books as a communication medium at the Museum Kepresidenan RI Balai Kirti. The research method used is qualitative, with data collection through in-depth interviews with museum staff and surveys of visitors. Data were analyzed using the Cognitive Theory of Multimedia Learning (CTML) to understand how the design of the digital book affects the user experience, as well as SWOT analysis to map the strengths, weaknesses, opportunities, and threats related to its implementation. The research results highlight that interactive digital books offer opportunities to improve museum information accessibility and visitor engagement. Its implementation is also influenced by factors such as the quality of the book's content, audio-visual elements, language use, and the richness of the information presented. This study concludes that the success of interactive digital books as a museum communication medium requires a comprehensive strategy that considers the various aspects.